Voices of globalization - Wejnert, Barbara (Research in political sociology ;, 2013)
This volume addresses issues of modern globalized development posing a question whether it symbolizes progress or regress for worlds societies. The papers focus on economic and political issues experienced by countries at this time of rapid diffusion of democracy and of the global market economy. A range of pertinent political issues are discussed, such as international migration, environmental protection and green energy, human rights, tolerance and equality, and economic justice. The concluding chapter provides a summary of presented topics in form of a discussion forum on outcomes of global development.